Play and Learn with an Intelligent Robot: Enhancing the Therapy of Hearing-Impaired Children - Ioannou, Andri; Andreva, Anna (My University, 2019)
This study suggests an innovative way of using an intelligent robot to support speech therapy for hearing impaired children through play. Although medical technology (e.g., hearing aid, cochlear implant) for children with hearing impairment has advanced significantly, the amplification itself does not provide optimal development of hearing and speaking; it must be combined with specialized therapy. The present study focuses on the use of the humanoid robot NAO in auditory-verbal therapy, an approach to the development of auditory and verbal skills, which does not allow lipreading or other non-verbal cues to facilitate communication. NAO does not have a human mouth and therefore children with hearing impairment cannot do lipreading; this unique characteristic of the technology has been successfully used in the study to create playful and engaging auditory-verbal therapy sessions for six kindergarten hearing impaired children, allowing them to improve their ability to follow instructions using the hearing aid/cochlear implant rather than visual clues in the environment. Our results, although preliminary, seem to encourage further research in supporting hearing-impaired children via play with intelligent robots.
Keywords: Auditory-Verbal therapy; Deaf; Hearing impairment; Humanoid robot; Intelligent robot; NAO; Playful learning; Special education; Speech therapy; Technology-enhanced learning